PENGARUH KUALITAS JASA TERHADAP LOYALITAS KONSUMEN YANG DIMEDIASI OLEH KEPUASAN KONSUMEN DI RESTORAN LOTTERIA PLAZA SEMANGGI - Amanda Marcelia (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2017)
This research aims to confirm the effect of service quality on consumer loyalty mediated by customer satisfaction at Lotteria restaurant. In collecting data, the authors distributed 140 questionnaires to respondents whom are Lotteria restaurant visitors using convenience sampling techniques. The collected data was analyzed using path analysis and bootstrapping tests. The results of the study indicate that service quality has a direct influence on loyalty and service quality can have an indirect effect mediated by customer satisfaction.